Antagonistic potential of rhizosphere bacteria from citrus plants in East Kalimantan against Lasiodiplodia theobromae - Triasih, Unun; Dwiastuti, Mutia Erti; Anggraeni, Listy; Suharjono; Fatoni, Muhamad Rizki; Agustina, Nensi (Penerbit Universiti Kebangsaan Malaysia, 2026)
East Kalimantan is one of the central areas for the development of Siamese oranges (Citrus nobilis) in eastern Indonesia. However, diplodia stem rot disease caused by Lasiodiplodia theobromae causes low productivity. Alternative control of those pathogens using indigenous antagonist bacteria is environmentally friendly. This study aims to analyse the diversity of rhizosphere bacteria in citrus plants in dry land and swamps from East Kalimantan and evaluate their potential to inhibit the growth of L. theobromae in vitro. The research consisted of rhizosphere bacteria isolation, analysis of bacterial diversity, potency assay of each isolate to inhibit the growth of L. theobromae, and identification of potential bacteria isolates based on 16S rDNA similarity. The results showed that 17 isolates of non-pathogenic rhizosphere bacteria, three of which, namely T4, T13, and T14, have the highest potency to inhibit the growth of L. theobromae. Among those isolates, the T13 bacterial isolate had the highest potency to inhibit that pathogenic fungus at logarithmic and stationary growth phases. Isolate T4, based on 16S rDNA sequence similarity, was identified as Bacillus subtilis, while T13 and T14 were identified as Pseudomonas aeruginosa.